Longitudinal association between somatic symptoms and suicidal ideation in adults with major depressive disorder - Yiming, Subinuer; Liao, Yuhua; Li, Yanzhi; Zhou, Wenjing; Zhao, Hao; Chen, Ruiying; Zhang, Qindan; Liu, Yifeng; Zhang, Huimin; Dri, Christine E.; McIntyre, Roger S.; Wang, Wanxin; et al. (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) is often accompanied by somatic symptoms, but their longitudinal relationship with suicidal ideation (SI) remains insufficiently characterized. This longitudinal study in MDD patients aimed to (1) examine the associations between somatic symptoms (including total, pain, autonomic, energy, and CNS symptoms) and SI, and (2) investigate potential non-linear relationships among somatic symptoms and their subtypes with SI.MethodsData was collected from patients with MDD in the Depression Cohort in China. The 28-item Somatic Symptoms Inventory (SSI) was used to assess somatic symptoms. SI was measured using the Beck Scale for Suicide Ideation (BSSI). Assessments were conducted at baseline and at weeks 4, 8, 12, 24, 48, and 72. Generalized estimating equations were utilized for exploring the associations of somatic symptoms and their subtypes with SI. GEE across three distinct models: Model 1 (unadjusted); Model 2 adjusted for sociodemographic and lifestyle factors; and Model 3 additionally adjusted for clinical characteristics. All models accounted for baseline SI.ResultsThese studies consisted of 1274 individuals with MDD (mean [SD], 27.7 [6.8] years; 399 (31.3%) males). The adjusted odds ratios (ORs) for SI across quartiles of total somatic symptom scores were 1.0 (reference), 0.95 (95% CI: 0.85-1.07, P = 0.419), 1.20 (95% CI: 1.03-1.41, P = 0.022), and 1.71 (95% CI: 1.39-2.11, P < 0.001) for quartiles 1,2, 3, and 4, respectively. Pain, autonomic, energy, and CNS symptoms showed similar results. A non-linear association (P for nonlinear < 0.001) was observed between total somatic symptom scores and SI. When the total somatic symptom score is below 49, the risk of SI remains at a relatively low level. However, when these scores exceeded the mentioned values, the risk of SI increases rapidly.ConclusionsOur findings suggest that in patients with MDD, there is a significant association between somatic symptoms and their subtypes with SI. Notably, the risk of SI is significantly increased by somatic symptoms in a nonlinear manner. These findings highlight the necessity of addressing somatic symptoms in the management of depression and emphasize the importance of developing targeted interventions to mitigate suicide risk in this vulnerable population.